2
$\begingroup$

Problem

Given a Hilbert space $\mathcal{H}$.

Consider a spectral measure: $$E:\mathcal{B}(\mathbb{C})\to\mathcal{B}(\mathcal{H})$$

Denote its probability measures by: $$\nu_\varphi(A):=\|E(A)\varphi\|^2$$

Introduce the pure-point space: $$\mathcal{H}_0(E):=\{\varphi:\exists\#\Lambda_0\leq\aleph_0:\nu_\varphi(\Lambda_0)=\nu_\varphi(\Omega)\}$$

Construct its normal operator: $$\varphi\in\mathcal{D}(N):\quad\langle N\varphi,\chi\rangle=\int_\mathbb{C}\lambda\mathrm{d}\langle E(\lambda)\varphi,\chi\rangle\quad(\chi\in\mathcal{H})$$

Regard its eigenspace: $$\mathcal{E}_\lambda=\{\varphi:N\varphi=\lambda\varphi\}:\quad\mathcal{E}(N):=\cup_{\lambda}\mathcal{E}_\lambda$$

Then one has: $$\mathcal{H}_0(E)=\overline{\langle\mathcal{E}(N)\rangle}$$

How to prove this?

Reference

This thread is related to: Spectral Spaces (I)

$\endgroup$
1
$\begingroup$

Prework

On the one side one has: $$\nu_\varphi(\Lambda_0)=\nu_\varphi(\Omega)\iff E(\Lambda_0)\varphi=\varphi$$

On the other side one has: $$N\varphi=\lambda\varphi\iff E(\lambda)\varphi=\varphi$$

(So both are translated!)

Subwork

So eigenspaces are closed: $$\overline{\mathcal{E}_\lambda}=\overline{\mathcal{R}E(\lambda)}=\mathcal{R}E(\lambda)=\mathcal{E}_\lambda$$ and mutually orthogonal: $$\langle\varphi,\psi\rangle=\langle E(\kappa)\varphi,E(\lambda)\psi\rangle=0\quad(\kappa\neq\lambda)$$

Thus, they admit an ONB: $$\mathcal{S}(N):=\bigcup_\lambda\mathcal{S}_\lambda:\quad\overline{\langle\mathcal{E}(T)\rangle}=\overline{\langle\mathcal{S}(N)\rangle}\quad\left(\mathcal{E}_\lambda=\overline{\langle\mathcal{S}_\lambda\rangle}\right)$$ (Note it may be uncountable!)

Main Work

By strong countable additivity: $$\varphi\in\mathcal{H}_0(E)\implies\varphi=E(\Lambda_0)\varphi=\sum_{\lambda\in\Lambda_0}E(\lambda)\varphi=:\sum_{\lambda\in\Lambda_0}\varphi_\lambda\implies\varphi\in\overline{\langle\mathcal{E}(N)\rangle}$$

Conversely one writes: $$\varphi\in\overline{\langle\mathcal{E}(T)\rangle}:\quad\varphi=\sum_{\chi\in\mathcal{S}(T)}a_\chi\chi\quad(N\chi=\lambda_\chi\chi)$$

By summability one has: $$\Lambda_0:=\{\lambda_\chi:a_\chi\neq0\}:\quad\#\Lambda_0\leq\aleph_0$$

Therefore one checks: $$E(\Lambda_0)\varphi=\sum_{\lambda\in\Lambda_0}\sum_{\chi\in\mathcal{S}(T)}E(\lambda)a_\chi\chi=\sum_{\chi\in\mathcal{S}(T)}a_\chi\chi=\varphi$$

That gives the converse!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.